ANALYSIS OF INFLECTIONAL MORPHEME FROM A SHORT STORY ENTITLED THE THREE LITTLE PIGS RETOLD BY FLORA ANNIE STEEL (1922) - Cahyono, Bayu Imam; Fafida, Kun; Prastiwi, Dian; Fortinasari, Paulina Besty (Faculty of Education and Teachers Training, 2023)
This paper analyze inflectional morpheme from a short story The Three Little Pigs. The method the authors uses to analyze the data is quantitative and qualitative descriptive methods. The purpose of this research is to investigate inflectional affixes, particularly the type of inflectional affixes and the function of inflectional morpheme. The results showed 47 affixes that obtained prefixes (0) and suffixes (47). These affixes are “-s” (10), “-ed” (27), “-er” (1), “-est” (1), “-‘s” (1), “-en” (1), “-ing” (5), “-es” (1). The authors analyze affixes based on their functions as noun maker, verb maker, adjective maker, and adverb maker. The results show data for noun maker (25,54%), verb maker (61,70%), adjective maker (10,64%), and adverb maker (2,12%).